2021
DOI: 10.1371/journal.pone.0247498
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of fibroblast growth factor receptor 3 with mutant p53, and its association with worse outcome in oropharyngeal squamous cell carcinoma

Abstract: Fibroblast growth factor receptor 3 (FGFR3) is expressed in squamous cell carcinoma of the head and neck (SCCHN) including oropharyngeal squamous cell carcinoma (OPSCC) and is a potential therapeutic target. However, information on its correlation with other relevant cancer related proteins stratified by p16 status and its prognostic significance in OPSCC is limited. We examined FGFR3 expression and its correlation with clinical characteristics, p16 status, and mutant p53 (mp53) among 220 retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Due to the relatively small number of patients analyzed, our results should be interpreted with caution. Nevertheless, mRNA levels of FGFR3 mRNA have been associated with worse DFS in oropharyngeal squamous cell carcinoma (p = 0.005) [33] and in non-muscleinvasive bladder cancer (HR 3.78, p < 0.001) [34]. The FGFR3 mRNA level is also a negative prognostic factor for lung adenocarcinoma [35] and squamous cell laryngeal cancer [36], where high FGFR3 expression was significantly correlated with shorter overall survival (OS).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relatively small number of patients analyzed, our results should be interpreted with caution. Nevertheless, mRNA levels of FGFR3 mRNA have been associated with worse DFS in oropharyngeal squamous cell carcinoma (p = 0.005) [33] and in non-muscleinvasive bladder cancer (HR 3.78, p < 0.001) [34]. The FGFR3 mRNA level is also a negative prognostic factor for lung adenocarcinoma [35] and squamous cell laryngeal cancer [36], where high FGFR3 expression was significantly correlated with shorter overall survival (OS).…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of other markers, of which some have stem cell or tumor suppressor character, have also been studied by IHC for their possible predictive role in survival in HPV + TSCC, BOTSCC, and OPSCC, and here, only a few are described [ 33 , 34 , 42 , 104 ]. Early on, it was shown that having low CD44 intensity expression or CD98 expression was correlated with better survival irrespective of the HPV status in the tumors, while for tumor suppressor genes LRIG1-3 , only high LRIG1 expression was correlated with a better clinical outcome [ 33 , 34 , 42 ].…”
Section: The Search Of Prognostic or Targetable Biomarkers In Hpv + And Hpv − Tscc Botscc And Opsccmentioning
confidence: 99%
“…Using NGS in HNSCC, several different features have been disclosed between HPV + and HPV − cancers, including the potential of targeting some of them [ 28 , 43 , 49 , 67 , 105 , 106 , 107 , 108 , 109 ]. HPV + TSCC, BOTSCC, or OPSCC mainly presented mutations in the PIK3CA , notch homolog 1 translocation-associated (NOTCH1) , and FGFR3 genes, while HPV − tumors mainly had mutations in TP53 and cyclin-dependent kinase inhibitor 2A/B ( CDKN2A/B) [ 28 , 43 , 49 , 67 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. The prognostic values of some of these genes have been reported, but there are discrepancies between the studies, and the data should be taken with caution.…”
Section: The Search For Prognostic or Targetable Biomarkers In Hpv + And Hpv − Tscc Botscc And Opscmentioning
confidence: 99%
“…Conversely, FGFR3 mutations in HPV positive OPSCC are linked with improved disease free survival ( BERSANI et al, 2018 ). A further study highlighted that FGPR3 mutations were predominantly identified in an HPV negative OPSCC cohort, and in combination with mutant TP53 was linked with a worse overall prognosis ( Nannapaneni et al, 2021 ). Thus, extrapolating this data, combined mutant TP53 and mutated FGFR3 in the HPV positive OPSCC cohort is linked to improved OS.…”
Section: Human Papilloma Virus Positive Oropharyngeal Squamous Cell Carcinoma Linked With Disease Progression/recurrencementioning
confidence: 99%